Electrocatalytic Study of Paracetamol at a Single-Walled Carbon Nanotube/Nickel Nanocomposite Modified Glassy Carbon Electrode - Koh Sing Ngai; Wee Tee Tan; Zulkarnain Zainal; Ruzniza Mohd Zawawi; Joon Ching Juan (Advances in Materials Science and Engineering)
A rapid, simple, and sensitive method for the electrochemical determination of paracetamol was developed. A single-walled carbon nanotube/nickel (SWCNT/Ni) nanocomposite was prepared and immobilized on a glassy carbon electrode (GCE) surface via mechanical attachment. This paper reports the voltammetry study on the effect of paracetamol concentration, scan rate, pH, and temperature at a SWCNT/Ni-modified electrode in the determination of paracetamol. The characterization of the SWCNT/Ni/GCE was performed by cyclic voltammetry. Variable pressure scanning electron microscopy (VPSEM) and energy dispersive X-ray (EDX) spectrometer were used to examine the surface morphology and elemental profile of the modified electrode, respectively. Cyclic voltammetry showed significant enhancement in peak current for the determination of paracetamol at the SWCNT/Ni-modified electrode. A linear calibration curve was obtained for the paracetamol concentration between 0.05 and 0.50 mM. The SWCNT/Ni/GCE displayed a sensitivity of 64 mA M−1 and a detection limit of 1.17 × 10−7 M in paracetamol detection. The proposed electrode can be applied for the determination of paracetamol in real pharmaceutical samples with satisfactory performance. Results indicate that electrodes modified with SWCNT and nickel nanoparticles exhibit better electrocatalytic activity towards paracetamol.